Effects of neuromuscular electrical stimulation on arterial hemodynamic properties and body composition in paretic upper extremities of patients with subacute stroke - Shu-Chun Huang; Alice May-Kuen Wong; Yu-Fen Chuang; Yu-Chuan Liu; Wei-Lun Tsai; Jong-Shyan Wang (Biomedical Journal, 2014)
Background: Neuromuscular electric stimulation (NMES) induces repeated muscular contraction, possibly promoting the perfusion/oxygenation of the regional tissues. It remains unclear how NMES influences vascular hemodynamic property and segmental fluid distribution/composition in paretic extremities of hemiplegic patients. Methods: Eleven hemiplegic patients aged 62.6 ± 12.5 years in the subacute stage of stroke received NMES for paretic wrist extensor and flexor muscles 30 min daily, 5 days per week for 4 weeks. The non-paretic upper extremities (NPUE) that did not receive NMES served as control. Distribution of fluid to intra/extracellular milieu and arterial hemodynamic properties were determined by using the multi-frequency bioelectrical impedance and pulse wave analysis, respectively. Results: Compared with NPUE without NMES, paretic upper extremity (PUE) with NMES revealed a significantly less decrease in arterial blood flow, impedance quotient, slope quotient, and less increase in crest width and crest time of arterial pulse wave. NMES for 4 weeks increased body cell mass in PUE. Furthermore, NPUE without NMES reduced intracellular water, whereas PUE with NMES retarded loss of intracellular water after stroke. Conclusion: NMES therapy increases body cell mass, attenuates reduction of intracellular water, and alleviates arterial hemodynamic disturbance in PUE in subacute stroke. However, stroke-related physical deconditioning may negatively regulate body composition and impair hemodynamic function in NPUE.